Proton-Alpha Drift Instability of Electromagnetic Ion-Cyclotron Modes: Quasilinear Development - Lopez-Escobar, R (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The ability of space plasmas to self-regulate through mechanisms involving self-generated fluctuations is a topic of high interest. This paper presents the results of a new advanced quasilinear (QL) approach for the instability of electromagnetic ion-cyclotron modes driven by the relative alpha-proton drift observed in solar wind. For an extended parametric analysis, the present QL approach includes also the effects of intrinsic anisotropic temperatures of these populations. The enhanced fluctuations contribute to an exchange of energy between proton and alpha particles, leading to important variations of the anisotropies, the proton-alpha drift and the temperature contrast. The results presented here can help understand the observational data, in particular, those revealing the local variations associated with the properties of protons and alpha particles as well as the spatial profiles in the expanding solar wind. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.